2018
DOI: 10.18311/jnr/2018/22285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zamzam Water Extract of Curcuma zedoaria Treatment on Apoptosis, p53 and Bcl2 Protein Expression of T47D Cell Culture

Abstract: Introduction:People worldwide drink Zamzam water either medicinally or religiously. However, the effect of zamzam water extract of CZ in breast cancer cells remains unclear. Objective: To evaluate the zamzam water extract of CZ effect on cell apoptosis, p53 and Bcl2 protein expression in T47 D cells line culture. Methods: In the control group design, 16 Wells which was filled with T47 D cell line culture in the density of 5 x 10 4 /100 µl, were assigned into 4 groups. Control group (C-G), were only filled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…6,7 My own study that have been published indicated that the potential effect of water extract of CZ on T47D cells apoptosis remains low, less than 10%. 6 On the other hand, some evidences showed that both ethanol and ethyl acetate CZ extract has been proven capable of inducing apoptosis on various cancer cells. [6][7][8] However, the potential effect of ethanol and ethyl acetate CZ extract which one is more effective on T47D cells apoptosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7 My own study that have been published indicated that the potential effect of water extract of CZ on T47D cells apoptosis remains low, less than 10%. 6 On the other hand, some evidences showed that both ethanol and ethyl acetate CZ extract has been proven capable of inducing apoptosis on various cancer cells. [6][7][8] However, the potential effect of ethanol and ethyl acetate CZ extract which one is more effective on T47D cells apoptosis remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3 The decrease in BC mortality rate was attributable to screening program, improvement of treatment, earlier detection, and adjuvant therapy originate from botanical product. 3,5,6 Curcuma zedoaria (CZ) is a botanical product has been proven capable of inducing apoptosis on various cells such as Daltons Lymphoma Ascites (DLAs), Lung Carcinoma (A549), nasopharyngeal carcinoma (KB), leukemic (K562), and T47D cell lines. 6,7 My own study that have been published indicated that the potential effect of water extract of CZ on T47D cells apoptosis remains low, less than 10%.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations